Desempenho de sistema para tratamento de água residuária doméstica em assentamento da Chapada do Apodi, Apodi-RN - Freire Segundo, João Marcelo (Universidade Federal Rural do Semi-Árido, 2014)
The prevailing water scarcity in the Brazilian semiarid restricts the availability of drinking water, encouraging the practice of reuse primarily in agricultural production. This study aimed to analyze the performance of decanting-digester, wetland and solar reactor for the treatment of domestic sewage Milagres rural community, Apodi-RN. During the period of 1 to 22 December 2010, equivalent to 48 to 70 days after planting of Pennisetum purpureum, samples were collected from domestic sewage at different stages of treatment in four replications in time, to determine physicochemical and microbiological characteristics. The results indicated that there was significant removal of turbidity, total and fecal coliforms, biochemical oxygen demand, chemical oxygen demand, total suspended solids, total solids, phosphorus, total nitrogen and oils and greases using the set of decanting-digester with biological filters, wetland and solar reactor. The combination of solar radiation of 25.16 MJ m-2 d-1, 0.10 m blade effluent and solar exposure of 12 hours Apodi-RN allowed up to 99.99% removal of fecal coliforms and effluent treated introduces microbiological standard that meets the state guidelines for fertigation of crops not eaten raw
Performance of system for treating domestic wastewater in rural community of Chapada do Apodi, Apodi-RN
Keywords: Pollution control; Water scarcity; reuse; Controle de poluição; Escassez de água; Reuso; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM